High-strength durable hot Tem fabric as well as preparation method and application thereof
By forming enhanced nanocoats and acid- and alkali-resistant coatings on the Gertem fabric, the problem of damage to the fabric during washing and use is solved, which improves durability and strength, extends service life and maintains comfort.
Patent Information
- Application Number
- CN202411834542.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-12-13
AI Technical Summary
Gertem fabrics are prone to damage during washing and use, resulting in weakening of heating function, and insufficient durability and strength, which affects service life.
Using a multi-layer design of enhanced nanocoating and acid-base-resistant coating, a high-strength durable fabric is formed by impregnating carbon nanotube slurry on the Gertem fabric layer and coating silicone composite modified polyurethane coating.
It significantly improves the wear resistance, acid and alkali resistance and mechanical strength of the fabric, extends the service life, simplifies the use requirements, and maintains softness and wear comfort.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fabric coatings and relates to a high-strength and durable thermal thermo fabric and a preparation method and application thereof. Background Art
[0002] Thermo fabric is an innovative high-tech functional fabric, known for its excellent warmth retention and comfortable wearing experience. The fabric introduces heat-generating polymers into the fiber, giving the fabric the ability to absorb and reflect human far infrared rays, which are then converted into heat energy to achieve the effect of heat storage and warmth retention. This technology not only enables the Thermo fabric to heat up quickly the moment it touches the skin, but also maintains a stable temperature for a long time, providing lasting warmth.
[0003] Compared with traditional thermal insulation materials, Retemu fabric can achieve efficient thermal insulation without relying on heavy fillings, so it is lighter, softer and more comfortable to wear. In addition, it has good breathability and moisture absorption and perspiration performance, which can effectively regulate body surface temperature and avoid discomfort caused by excessive sweating. Retemu fabric is widely used in winter thermal clothing, such as underwear, base shirts and home textile products, providing users with a new thermal insulation solution in cold seasons. Its unique heating mechanism and comfortable wearing experience make it a leader in the field of modern thermal insulation fabrics.
[0004] Although hot tam fabric is popular for its excellent warmth retention and comfortable wearing experience, it also has certain limitations that affect its performance in certain applications and the user experience. In order to maintain the heat and warmth retention of hot tam fabric, it is often necessary to follow specific washing and maintenance methods, such as using mild detergents and avoiding high-temperature drying or ironing. These cumbersome requirements will bring inconvenience to daily use. If improperly maintained, the heating function of the fabric may be weakened or completely ineffective, thus affecting the wearing experience and product life. Secondly, on the basis of complying with specific washing and maintenance, the heat generation of hot tam fabric after long-term use and multiple washings will still face a gradual downward trend. This is because the heating masterbatch may wear or fall off during repeated friction and washing, resulting in a weakening of the heating effect of the fabric. Therefore, the durability of hot tam fabric is an important consideration affecting the service life of the fabric. In addition, based on the highly soft characteristics of hot tam fabric, it often leads to its low strength. After multiple wearing and friction, the fabric is more likely to wear or break, thus affecting its service life and durability.
[0005] In summary, although Retemu fabrics have significant advantages in terms of warmth and comfort, they still have some shortcomings in terms of washing and maintenance, durability, scope of application, breathability, and environmental sustainability. These limitations need to be considered comprehensively when selecting and using Retemu fabrics to ensure the best user experience and product value. Summary of the invention
[0006] In view of the above problems existing in the prior art, the present invention provides a high-strength and durable thermal temu fabric and a preparation method and application thereof.
[0007] One object of the present invention is achieved by the following technical solutions:
[0008] A high-strength and durable hot tam fabric comprises a hot tam fabric layer, a reinforced nano coating located above the hot tam fabric layer, and an acid- and alkali-resistant coating located above the reinforced nano coating.
[0009] The enhanced nano coating is made by dipping a hot-tem surface layer into a carbon nanotube slurry; the acid-base resistant coating is made by coating an organic silicon composite modified polyurethane coating slurry on the upper surface of the enhanced nano coating.
[0010] Preferably, the carbon nanotube slurry is prepared from the following raw materials in parts by weight: 1-30 parts of carbon nanotubes, 0.1-5 parts of dispersant, 1-5 parts of stabilizer, and 10-80 parts of polar solvent.
[0011] Preferably, the carbon nanotubes have a diameter of 1-20 nm and a length of 1-20 μm.
[0012] Preferably, the dispersant includes one or more of polyvinyl pyrrolidone, sodium polyacrylate, and polyethylene glycol. The dispersant can evenly disperse the carbon nanotube solid particles in the liquid medium to prevent the particles from agglomerating, and reduce the surface tension of the liquid medium, improve the wettability of the solid particles, and make the particles more easily surrounded and dispersed by the liquid. The present invention uses a polymer dispersant to form a protective film by adsorbing on the surface of the particles, and provides steric hindrance through the long chain structure to prevent direct contact and aggregation between the particles.
[0013] Preferably, the stabilizer includes one or more of polyoxyethylene ether, polyvinyl alcohol, and polyacrylic acid. The main function of the stabilizer is to maintain the long-term stability of the dispersed system and prevent the particles from re-aggregating or precipitating. The stabilizer can slow down and prevent the sedimentation of particles in the liquid, maintain the uniformity of the system, and prevent the particles from flocculating during storage or use.
[0014] Preferably, the polar solvent includes one or more of deionized water, ethanol, isopropanol, N,N-dimethylformamide, and N-methylpyrrolidone.
[0015] Preferably, the method for preparing the carbon nanotube slurry comprises the following steps: adding carbon nanotubes into a polar solvent, then adding a dispersant to disperse them uniformly, and then adding a stabilizer and continuing to stir them uniformly to obtain the carbon nanotube slurry.
[0016] In the method for preparing the carbon nanotube slurry, preferably, ultrasonic treatment is used for dispersion, the ultrasonic dispersion frequency is 10-60 kHz, the ultrasonic dispersion power is 50-500 W, and the ultrasonic dispersion time is 10-60 min.
[0017] Preferably, the organosilicon composite modified polyurethane coating slurry is prepared from the following raw materials in parts by weight: 10-50 parts of polyurethane monomer, 10-20 parts of methacrylate, 10-30 parts of organosilicon monomer, 0.1-5 parts of catalyst, 1-5 parts of surfactant, and 20-50 parts of organic solvent.
[0018] Preferably, the polyurethane monomer is a combination of isocyanate and polyol.
[0019] Preferably, the isocyanate includes one or more of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), and lysine diisocyanate (LDI).
[0020] Preferably, the polyol includes one or more of polyoxypropylene glycol, polytetramethylene glycol, polyethylene glycol adipate, polybutylene glycol adipate, polycarbonate diol, and polycaprolactone diol.
[0021] Preferably, the mass ratio of the isocyanate to the polyol is (1-5):(1-10).
[0022] Preferably, the methacrylate is one or both of methyl methacrylate and butyl methacrylate.
[0023] The present invention introduces methacrylate to modify the process of isocyanate and polyol forming polyurethane through polycondensation. The double bond in methacrylate can undergo Michael addition reaction with isocyanate (-NCO), the double bond of methacrylate is opened, and a new carbon-nitrogen bond is formed with the isocyanate group; secondly, the ester group (-COO-) in methacrylate can undergo ester exchange reaction with the hydroxyl group (-OH) in the polyol to generate new esters and alcohols. In the above reaction process, methacrylate, isocyanate and polyol participate in copolymerization reaction together to form a modified polyurethane material with multiple functional groups, which can be applied to the coating of hot temu fabric to provide better strength performance and durability.
[0024] Preferably, the organic silicon monomer includes one or more of amino silicone oil, epoxy silicone oil, hydroxy silicone oil, carboxyl silicone oil, polydimethylsiloxane, and terminal hydroxyl polydimethylsiloxane.
[0025] Silicone has good chemical stability and is well compatible with modified polyurethane. When silicone is introduced into the polyurethane system, it can form a stable cross-linked network structure in the fabric coating; secondly, the presence of silicone molecular segments helps to reduce the surface free energy of the entire polymer network, thereby improving the fabric's ability to repel liquids such as water, oil, and sweat, and enhancing corrosion resistance and acid and alkali resistance; at the same time, because the silicone segments themselves are relatively soft and have good elasticity, when they are introduced into the modified polyurethane, they can provide a certain strength while maintaining the overall flexibility and ductility of the Hotram fabric itself.
[0026] Preferably, the catalyst comprises: 50-70 wt % of a base catalyst and 30-50 wt % of an organic metal catalyst.
[0027] Preferably, the base catalyst includes one or more of sodium ethoxide, sodium hydride, sodium amide, dimethylcyclohexylamine, and triethylenediamine.
[0028] Preferably, the organic metal catalyst includes one or more of dibutyltin dilaurate, stannous octoate, and zinc diacetate.
[0029] Preferably, the surfactant includes one or more of a nonionic surfactant, an anionic surfactant, and a cationic surfactant.
[0030] More preferably, the surfactant includes one or more of polyoxyethylene ether, polyoxyethylene alkylphenol ether, polyoxyethylene fatty alcohol ether, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and hexadecyltrimethylammonium bromide.
[0031] Preferably, the organic solvent includes one or more of ethyl acetate, toluene, xylene, n-heptane, cyclohexane, propylene glycol methyl ether acetate, dipropylene glycol methyl ether, and ethylene glycol butyl ether.
[0032] Preferably, the preparation method of the organosilicon composite modified polyurethane coating slurry comprises the following steps: adding a composition of polyurethane monomers, methyl acrylate and a catalyst into an organic solvent and stirring them to obtain a modified polyurethane through a copolymerization reaction; then adding an organosilicon monomer and continuing to stir to perform a cross-linking reaction; and then adding a surfactant and stirring evenly to obtain the organosilicon composite modified polyurethane coating slurry.
[0033] In the method for preparing the organosilicon composite modified polyurethane coating slurry, preferably, the copolymerization reaction temperature is 50-90° C. and the reaction time is 1-5 h.
[0034] In the method for preparing the organosilicon composite modified polyurethane coating slurry, preferably, the cross-linking reaction temperature is 30-60° C., and the reaction time is 1-5 hours.
[0035] In the method for preparing the organosilicon composite modified polyurethane coating slurry, preferably, a surfactant is added and stirred for 10 to 30 minutes.
[0036] Another object of the present invention is achieved by the following technical solutions:
[0037] A method for preparing a high-strength and durable hot-therm fabric, the method comprising the following steps: dipping a hot-therm fabric layer into a carbon nanotube slurry, and forming an acid- and alkali-resistant coating after drying; then applying an organosilicon composite modified polyurethane coating slurry on the acid- and alkali-resistant coating, and forming a reinforced nano coating after drying and curing to obtain the high-strength and durable hot-therm fabric.
[0038] Preferably, the drying temperature of the enhanced nano coating is 30-80° C., and the drying time is 1-50 hours.
[0039] Preferably, the acid- and alkali-resistant coating has a drying temperature of 30-80° C., a drying time of 1-20 hours, a curing temperature of 80-120° C., and a curing time of 10-60 minutes.
[0040] Preferably, the thickness of the enhanced nano coating is 0.01-0.1 mm.
[0041] Preferably, the thickness of the acid- and alkali-resistant coating is 0.1-1 mm.
[0042] Another object of the present invention is achieved by the following technical solutions:
[0043] The invention discloses an application of a high-strength and durable thermal temu fabric in the preparation of clothing and household items.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] 1. The present invention provides a high-strength and durable Thermotec fabric, which significantly improves the wear resistance of the fabric by impregnating carbon nanotube slurry on the Thermotec fabric layer to form a reinforced nano coating. Carbon nanotubes have extremely high strength and hardness, and can effectively resist the wear caused by repeated wearing and friction; the organosilicon composite modified polyurethane coating slurry is applied to the reinforced nano coating to form an acid and alkali resistant coating. This coating has excellent chemical corrosion resistance, can protect the fabric from erosion by acid and alkali environments, effectively simplify the user's usage requirements, and extend the service life; the combination of carbon nanotubes and organosilicon modified polycondensation polyurethane coating not only improves the wear resistance and acid and alkali resistance of the fabric, but also enhances its mechanical strength and tear resistance, making the fabric more durable.
[0046] 2. The high-strength and durable hot-tem fabric provided by the present invention innovatively adopts a multi-coating design of enhanced nano-coating and acid- and alkali-resistant coating. Through the optimal coating material and coating parameter setting, the hot-tem fabric can maintain high softness and ensure wearing comfort while improving its strength performance. Due to the multiple protective effects of the coating, the fabric is not easily damaged during use, which reduces the replacement frequency of users and reduces maintenance costs.
[0047] 3. The present invention provides a method for preparing a high-strength and durable thermal temu fabric, which adopts a unique process of first impregnating an enhanced nano-coating and then applying an acid-resistant and alkali-resistant coating. This method not only simplifies the production process, but also significantly improves the comprehensive performance of the fabric. The method can complete the molding of the entire coating system through only one curing process. During the curing process of the organosilicon-modified condensation polyurethane coating, the modified polyurethane component in the coating can further assist in enhancing the fixation of carbon nanotubes in the nano-coating, thereby forming a tightly integrated whole. This integrated curing process not only simplifies the production process, but also ensures good bonding between the coatings, enhancing the overall durability and stability. The preparation method is simple and easy to operate, with clear operating steps, easy to control, and suitable for large-scale industrial production. DETAILED DESCRIPTION
[0048] The technical solution of the present invention is further described below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
[0049] Example 1
[0050] The carbon nanotube slurry of this embodiment is prepared from the following raw materials in parts by weight: 10 parts of carbon nanotubes (Xianfeng Nano, diameter 1-2 nm, length 1-3 μm), 2 parts of polyvinyl pyrrolidone, 3 parts of polyoxyethylene ether, 50 parts of deionized water, and 20 parts of ethanol.
[0051] The preparation method of the carbon nanotube slurry of this embodiment includes the following steps: adding deionized water and ethanol to a reaction container, and stirring evenly at room temperature to form a mixed solvent; slowly adding carbon nanotubes to the mixed solvent, and turning on an ultrasonic disperser at a frequency of 40kHz, a power of 300W, and ultrasonic dispersion for 30 minutes to ensure that the carbon nanotubes are evenly dispersed in the solvent to avoid agglomeration; adding polyvinyl pyrrolidone and continuing to stir for 10 minutes to ensure that the dispersant is adsorbed on the surface of the carbon nanotubes to form a protective film to prevent direct contact and aggregation between particles; adding polyoxyethylene ether and continuing to stir for 10 minutes to ensure that the stabilizer is evenly distributed in the solution to improve the long-term stability of the dispersion system and prevent the carbon nanotubes from re-aggregating or settling; finally obtaining the carbon nanotube slurry, which is stored in a dry, light-proof environment for future use.
[0052] The organic silicon composite modified polyurethane coating slurry of this embodiment is prepared from the following raw materials in parts by weight: 15 parts of diphenylmethane diisocyanate, 22 parts of polyoxypropylene glycol, 13 parts of methyl methacrylate, 15 parts of amino silicone oil, 2 parts of sodium ethoxide, 1 part of dibutyltin dilaurate, 2 parts of sodium dodecyl sulfate, 30 parts of ethyl acetate, and 20 parts of toluene.
[0053] The preparation method of the organic silicon composite modified polyurethane coating slurry of the present embodiment comprises the following steps: adding diphenylmethane diisocyanate, polyoxypropylene glycol and methyl methacrylate into a reaction container, and adding ethyl acetate and toluene, and stirring evenly at room temperature using a stirrer; adding sodium ethoxide and dibutyltin dilaurate, heating to 70°C, and continuously stirring for 2 hours to carry out copolymerization reaction to obtain modified polyurethane; after adding amino silicone oil, continuously stirring at 50°C for 2 hours to carry out cross-linking reaction, so that the organic silicon monomer fully participates in the reaction and forms a stable cross-linking network; adding sodium dodecyl sulfate and continuing stirring for 20 minutes to obtain the organic silicon composite modified polyurethane coating slurry.
[0054] The preparation method of the high-strength and durable hot-tem fabric of this embodiment includes the following steps: immersing the hot-tem fabric layer in the carbon nanotube slurry, slowly pulling the fabric until there is no slurry dripping, placing the immersed fabric in a ventilated environment, and drying it at 60°C for 24 hours to form a reinforced nano coating with a thickness of 0.05 mm; applying the organic silicon composite modified polyurethane coating slurry on the upper surface of the reinforced nano coating, controlling the coating thickness to 0.3 mm, placing the coated fabric in a ventilated environment, and drying it at 60°C for 12 hours; finally, placing the fabric in an oven and curing it at 100°C for 30 minutes to form an acid- and alkali-resistant coating to obtain the high-strength and durable hot-tem fabric.
[0055] Example 2
[0056] The difference between this embodiment and embodiment 1 is that the carbon nanotube slurry is prepared from the following raw materials in parts by weight: 15 parts of carbon nanotubes (Xianfeng Nano, diameter 1-2 nm, length 1-3 μm), 3 parts of sodium polyacrylate, 4 parts of polyvinyl alcohol, 40 parts of deionized water, and 30 parts of isopropanol. The rest is the same as in embodiment 1.
[0057] Example 3
[0058] The difference between this embodiment and embodiment 1 is that the organic silicon composite modified polyurethane coating slurry is prepared from the following raw materials in parts by weight: 12 parts of toluene diisocyanate, 25 parts of polycarbonate diol, 15 parts of butyl methacrylate, 17 parts of carboxyl silicone oil, 1.5 parts of dimethylcyclohexylamine, 1 part of stannous octoate, 2 parts of polyoxyethylene ether, 30 parts of ethyl acetate, and 20 parts of toluene. The rest is the same as in embodiment 1.
[0059] Example 4
[0060] The difference between this embodiment and embodiment 1 is that the preparation method of high-strength and durable hot-tem fabric comprises the following steps: immersing the hot-tem fabric layer in carbon nanotube slurry, slowly pulling the fabric until there is no slurry dripping, placing the immersed fabric in a ventilated environment, drying at 60°C for 24 hours, and forming a reinforced nano coating with a thickness of 0.1 mm; applying the organic silicon composite modified polyurethane coating slurry on the upper surface of the reinforced nano coating, controlling the coating thickness to 0.5 mm, placing the coated fabric in a ventilated environment, and drying at 60°C for 12 hours; finally, placing the fabric in an oven, curing at 100°C for 30 minutes, forming an acid- and alkali-resistant coating, and obtaining the high-strength and durable hot-tem fabric. The rest is the same as embodiment 1.
[0061] Comparative Example 1
[0062] The difference between this comparative example and Example 1 is that the modified polyurethane coating slurry without silicone compound is used in the acid-base resistant coating, and the rest is the same as Example 1.
[0063] The modified polyurethane coating slurry of this comparative example is prepared from the following raw materials in parts by weight: 15 parts of diphenylmethane diisocyanate, 22 parts of polyoxypropylene glycol, 13 parts of methyl methacrylate, 2 parts of sodium ethoxide, 1 part of dibutyltin dilaurate, 2 parts of sodium dodecyl sulfate, 30 parts of ethyl acetate, and 20 parts of toluene.
[0064] The preparation method of the modified polyurethane coating slurry of the comparative example comprises the following steps: adding diphenylmethane diisocyanate, polyoxypropylene glycol and methyl methacrylate into a reaction container, and adding ethyl acetate and toluene, and stirring evenly at room temperature using a stirrer; adding sodium ethoxide and dibutyltin dilaurate and heating to 70°C, and continuously stirring for 2 hours to perform a copolymerization reaction to obtain a modified polyurethane; adding sodium dodecyl sulfate and continuously stirring for 20 minutes to obtain the modified polyurethane coating slurry.
[0065] Comparative Example 2
[0066] The difference between this comparative example and Example 1 is that an organosilicon composite modified isocyanate coating slurry is used in the acid-base resistant coating, and the rest is the same as Example 1.
[0067] The organic silicon composite modified isocyanate coating slurry of this comparative example is prepared from the following raw materials in parts by weight: 15 parts of diphenylmethane diisocyanate, 13 parts of methyl methacrylate, 15 parts of amino silicone oil, 2 parts of sodium ethoxide, 1 part of dibutyltin dilaurate, 2 parts of sodium dodecyl sulfate, 30 parts of ethyl acetate, and 20 parts of toluene.
[0068] The preparation method of the comparative example organosilicon modified isocyanate coating slurry comprises the following steps: adding diphenylmethane diisocyanate and methyl methacrylate into a reaction container, and adding ethyl acetate and toluene, and stirring evenly at room temperature using a stirrer; adding sodium ethoxide and dibutyltin dilaurate and heating to 70°C, and stirring continuously for 2 hours to obtain modified isocyanate; after adding amino silicone oil, stirring continuously for 2 hours at 50°C for cross-linking reaction; adding sodium dodecyl sulfate and continuing stirring for 20 minutes to obtain the organosilicon composite modified isocyanate coating slurry.
[0069] Comparative Example 3
[0070] The difference between this comparative example and Example 1 is that an organosilicon composite modified polyol coating slurry is used in the acid-base resistant coating, and the rest is the same as Example 1.
[0071] The organic silicon composite modified polyol coating slurry of this comparative example is prepared from the following raw materials in parts by weight: 22 parts of polyoxypropylene glycol, 13 parts of methyl methacrylate, 15 parts of amino silicone oil, 2 parts of sodium ethoxide, 1 part of dibutyltin dilaurate, 2 parts of sodium dodecyl sulfate, 30 parts of ethyl acetate, and 20 parts of toluene.
[0072] The preparation method of the comparative example silicone composite modified polyol coating slurry comprises the following steps: adding polyoxypropylene glycol and methyl methacrylate into a reaction container, and adding ethyl acetate and toluene, and stirring evenly at room temperature using a stirrer; adding sodium ethoxide and dibutyltin dilaurate and heating to 70°C, and stirring continuously for 2 hours to obtain a modified polyol; after adding amino silicone oil, stirring continuously for 2 hours at 50°C for a cross-linking reaction; adding sodium dodecyl sulfate and continuing stirring for 20 minutes to obtain the silicone composite modified polyol coating slurry.
[0073] Comparative Example 4
[0074] The difference between this comparative example and Example 1 is that an organosilicon composite polyurethane coating slurry is used in the acid-base resistant coating, and the rest is the same as Example 1.
[0075] The silicone composite polyurethane coating slurry of this comparative example is prepared from the following raw materials in parts by weight: 15 parts of diphenylmethane diisocyanate, 22 parts of polyoxypropylene glycol, 15 parts of amino silicone oil, 2 parts of sodium ethoxide, 1 part of dibutyltin dilaurate, 2 parts of sodium dodecyl sulfate, 30 parts of ethyl acetate, and 20 parts of toluene.
[0076] The preparation method of the comparative example silicone composite polyurethane coating slurry comprises the following steps: adding diphenylmethane diisocyanate and polyoxypropylene glycol into a reaction container, and adding ethyl acetate and toluene, and stirring evenly at room temperature using a stirrer; adding sodium ethoxide and dibutyltin dilaurate and heating to 70°C, and stirring continuously for 2 hours to carry out a copolymerization reaction to obtain polyurethane; after adding amino silicone oil, stirring continuously at 50°C for 2 hours to carry out a cross-linking reaction; adding sodium dodecyl sulfate and continuing to stir for 20 minutes to obtain the silicone composite polyurethane coating slurry.
[0077] Comparative Example 5
[0078] The difference between this comparative example and Example 1 is that in the preparation method of the hot temu fabric, the acid and alkali resistant coating is first applied, and then the enhanced nano coating is impregnated.
[0079] The raw materials and preparation method of the acid-base resistant coating and the enhanced nano coating of this comparative example are the same as those of Example 1.
[0080] The preparation method of the hot tam fabric of this comparative example comprises the following steps: applying a silicone composite modified polyurethane coating slurry to the upper surface of the hot tam fabric layer, controlling the coating thickness to be 0.3 mm, placing the coated fabric in a ventilated environment, drying at 60°C for 12 hours, placing the fabric in an oven, and curing at 100°C for 30 minutes to form an acid- and alkali-resistant coating; dipping the fabric in a carbon nanotube slurry, slowly pulling the fabric until no slurry drips, placing the impregnated fabric in a ventilated environment, and drying at 60°C for 24 hours to form a reinforced nano coating with a thickness of 0.05 mm to obtain the hot tam fabric.
[0081] Comparative Example 6
[0082] The difference between this comparative example and Example 1 is that in the preparation method of the hottemu fabric, only the enhanced nano coating is impregnated.
[0083] The raw materials and preparation method of the enhanced nano coating in this comparative example are the same as those in Example 1.
[0084] The preparation method of the hot tam fabric in this comparative example includes the following steps: immersing the hot tam fabric layer in the carbon nanotube slurry, slowly pulling the fabric until no slurry drips, placing the immersed fabric in a ventilated environment, and drying it at 60°C for 24 hours to form a reinforced nano coating with a thickness of 0.05 mm to obtain the hot tam fabric.
[0085] Comparative Example 7
[0086] The difference between this comparative example and Example 1 is that in the preparation method of the hottemu fabric, only the acid- and alkali-resistant coating is applied.
[0087] The raw materials and preparation method of the acid and alkali resistant coating of this comparative example are the same as those of Example 1.
[0088] The preparation method of the hot tam fabric in this comparative example comprises the following steps: applying a silicone composite modified polyurethane coating slurry to the upper surface of the hot tam fabric layer, controlling the coating thickness to be 0.3 mm, placing the coated fabric in a ventilated environment, drying at 60° C. for 12 hours, placing the fabric in an oven, and curing at 100° C. for 30 minutes to form an acid- and alkali-resistant coating to obtain the hot tam fabric.
[0089] Comparative Example 8
[0090] This comparative example uses conventional uncoated Retemu fabric for subsequent related performance testing.
[0091] The above-mentioned hot temu fabrics of the embodiment and the comparative example were subjected to relevant performance tests, and the specific test methods are as follows:
[0092] 1. Test the initial breaking strength of the Retem fabric according to GB / T3923.1-2013;
[0093] 2. Test the breaking strength of the Retem fabric after washing 30 times according to GB / T3923.1-2013, and calculate the breaking strength attenuation rate;
[0094] 3. Acid treatment of fabrics: Cut the fabrics into 40mm×100mm samples, put the samples into an acid solution with a bath ratio of 50:1 (the acid solution contains: 0.5g L-histidine hydrochloride monohydrate, 5g sodium chloride, 2.2g sodium dihydrogen phosphate dihydrate per liter, and the pH is adjusted to 5.5 with 0.1mol / L HCL) to completely wet it, and then place it at room temperature for 30 minutes, press and move the samples to ensure that the acid solution can penetrate well and evenly; take out the samples, pour off the residual liquid, use two glass rods to clamp the excess acid on the samples, clamp the samples between two glass plates to make the samples under a pressure of 12.5kPa and fix them, put the fixed samples into a constant temperature box at 37℃ for 4h; then hang them to dry at 60℃ for use;
[0095] Alkali treatment of fabrics: Cut the fabrics into 40mm×100mm samples, put the samples into an alkali solution with a bath ratio of 50:1 (each liter of the alkali solution contains: 0.5g L-histidine hydrochloride monohydrate, 5g sodium chloride, 5g disodium hydrogen phosphate dodecahydrate, and the pH of the test solution is adjusted to 8.0 with 0.1mol / L NaOH) to completely wet it, then place it at room temperature for 30 minutes, press and move the samples to ensure that the alkali solution can penetrate well and evenly; take out the samples, pour off the residual liquid, use two glass rods to clamp the excess alkali solution on the samples, clamp the samples between two glass plates so that the samples are under a pressure of 12.5kPa and fix them, put the fixed samples into a constant temperature box at 37℃ for 4h; then hang them to dry at 60℃ for use;
[0096] Then, the breaking strength of the Retem fabric after acid and alkali treatment was tested according to GB / T3923.1-2013, and the breaking strength attenuation rate was calculated;
[0097] The specific test results are shown in Table 1.
[0098] Table 1 Performance test results of examples and comparative examples
[0099] .
[0100] As shown in Table 1, it can be seen from Examples 1 to 4 that the high-strength and durable hot temu fabric prepared using the technical solution of the present invention has excellent strength performance. After washing 30 times and acid-base treatment, its breaking strength attenuation rate can be stabilized within 2%, which effectively increases the durability of the hot temu fabric in daily cleaning and long-term wear. It can be seen from Comparative Examples 1 to 4 that the acid-base resistant coating prepared without using the raw materials within the scope of the technical solution of the present invention cannot have a good cross-linked network, and cannot form a modified polyurethane material with multiple functional groups. After being applied to the hot temu fabric to form a coating, a large strength attenuation occurs after washing and acid-base treatment. It can be seen from Comparative Examples 5 to 8 that without using the enhanced nano coating and / or acid-base resistant coating of the present invention, and exchanging the coating order, the hot temu fabric will produce a large strength attenuation after washing and acid-base treatment, and the long-term use performance of the product cannot be guaranteed.
[0101] The various aspects, embodiments, and features of the present invention should be considered to be illustrative in all aspects and not limiting of the present invention, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.
[0102] In the preparation method of the present invention, the order of each step is not limited to the order listed. For those skilled in the art, without creative work, the order of each step is also within the protection scope of the present invention. In addition, two or more steps or actions can be performed simultaneously.
[0103] Finally, it should be noted that the specific embodiments described herein are merely examples of the present invention, and are not intended to limit the implementation methods of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described, or replace them in a similar manner. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.
Claims
1. A high-strength and durable thermal fabric, characterized in that: The high-strength and durable hot temu fabric comprises a hot temu fabric layer, a reinforced nano coating located above the hot temu fabric layer, and an acid- and alkali-resistant coating located above the reinforced nano coating; The enhanced nano coating is made of a heat-resistant surface layer immersed in a carbon nanotube slurry; The acid and alkali resistant coating is prepared by coating an organic silicon composite modified polyurethane coating slurry on the upper surface of the enhanced nano coating.
2. The high-strength and durable thermal fabric according to claim 1, characterized in that: The carbon nanotube slurry is prepared from the following raw materials in parts by weight: 1-30 parts of carbon nanotubes, 0.1-5 parts of dispersant, 1-5 parts of stabilizer, and 10-80 parts of polar solvent; The organic silicon composite modified polyurethane coating slurry is prepared from the following raw materials in parts by weight: 10-50 parts of polyurethane monomer, 10-20 parts of methacrylate, 10-30 parts of organic silicon monomer, 0.1-5 parts of catalyst, 1-5 parts of surfactant and 20-50 parts of organic solvent.
3. The high-strength and durable thermal temu fabric according to claim 2, characterized in that: The carbon nanotubes have a diameter of 1-20 nm and a length of 1-20 μm; The dispersant includes one or more of polyvinyl pyrrolidone, sodium polyacrylate, and polyethylene glycol; The stabilizer includes one or more of polyoxyethylene ether, polyvinyl alcohol, and polyacrylic acid; The polar solvent includes one or more of deionized water, ethanol, isopropanol, N,N-dimethylformamide, and N-methylpyrrolidone.
4. The high-strength and durable thermal temu fabric according to claim 2, characterized in that: The preparation method of the carbon nanotube slurry comprises the following steps: adding carbon nanotubes into a polar solvent, then adding a dispersant to disperse them uniformly, and then adding a stabilizer to continue stirring to obtain the carbon nanotube slurry.
5. The high-strength and durable thermal temu fabric according to claim 2, characterized in that: The polyurethane monomer is a composition of isocyanate and polyol; The isocyanate includes one or more of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, and lysine diisocyanate; The polyol includes one or more of polyoxypropylene glycol, polytetramethylene glycol, polyethylene glycol adipate, polybutylene glycol adipate, polycarbonate diol, and polycaprolactone diol; The mass ratio of the isocyanate to the polyol is (1-5):(1-10).
6. The high-strength and durable thermal fabric according to claim 2, characterized in that: The methacrylate is one or both of methyl methacrylate and butyl methacrylate; The organic silicon monomer includes one or more of amino silicone oil, epoxy silicone oil, hydroxy silicone oil, carboxyl silicone oil, polydimethylsiloxane, and terminal hydroxyl polydimethylsiloxane; The catalyst comprises: 50-70 wt% of a base catalyst and 30-50 wt% of an organic metal catalyst; The surfactant includes one or more of a nonionic surfactant, an anionic surfactant, and a cationic surfactant; The organic solvent includes one or more of ethyl acetate, toluene, xylene, n-heptane, cyclohexane, propylene glycol methyl ether acetate, dipropylene glycol methyl ether, and ethylene glycol butyl ether.
7. The high-strength and durable thermal temu fabric according to claim 2, characterized in that: The preparation method of the organosilicon composite modified polyurethane coating slurry comprises the following steps: adding polyurethane monomer, methacrylate and catalyst into an organic solvent and stirring them to obtain modified polyurethane through copolymerization reaction; then adding organosilicon monomer and continuing stirring to carry out cross-linking reaction; then adding surfactant and stirring evenly to obtain the organosilicon composite modified polyurethane coating slurry; the copolymerization reaction temperature is 50-90°C and the reaction time is 1-5h; the cross-linking reaction temperature is 30-60°C and the reaction time is 1-5h.
8. A method for preparing a high-strength and durable thermal temu fabric as claimed in any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: immersing the heat-resistant lining layer in carbon nanotube slurry, and forming an acid- and alkali-resistant coating after drying; then applying the organosilicon composite modified polyurethane coating slurry on the acid- and alkali-resistant coating, and forming a reinforced nano coating after drying and curing to obtain the high-strength and durable heat-resistant lining.
9. The preparation method according to claim 8, characterized in that: The drying temperature of the enhanced nano coating is 30-80°C and the drying time is 1-50h; The acid- and alkali-resistant coating has a drying temperature of 30 to 80° C., a drying time of 1 to 20 hours, a curing temperature of 80 to 120° C., and a curing time of 10 to 60 minutes; The thickness of the enhanced nano coating is 0.01-0.1 mm; The thickness of the acid and alkali resistant coating is 0.1-1 mm.
10. Use of the high-strength and durable ThermoTem fabric according to any one of claims 1 to 7 in the preparation of clothing and household items.
Citation Information
Patent Citations
Organosilicon-modified aqueous polyurethane-acrylate composite coating agent and preparation method thereof
CN102559031A
Organic silicon-polyurethane-acrylate composite coating agent crosslinked at room temperature and preparation method thereof
CN102585686A
High-temperature-resisting heating composite fabric and preparation method thereof
CN107263947A
Waterproof cushion fabric with organic Si nano-coating
CN109760395A
Preparation method of light absorption heating fabric
CN111705531A